The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12870-020-2321-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exogenous ascorbic acid and glutathione priming on mitochondrial structural and functional systems to alleviate aging damage in oat seeds

Abstract: Background: Loss of vigor caused by seed aging adversely affects agricultural production under natural conditions. However, priming is an economical and effective method for improving the vigor of aged seeds. The objective of this study was to test the effectiveness of exogenous ascorbic acid (ASC) and glutathione (GSH) priming in the repairing of aged oat (Avena sativa) seeds, and to test the hypothesis that structural and functional systems in mitochondria were involved in this process. Results: Oat seeds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…The mechanism through which priming treatments improve seed viability is related to the repair of cellular and mitochondrial components [ 11 ], synthesis of nucleic acids and proteins, and recovery of antioxidants [ 12 ]. Previous studies indicated that priming with exogenous substances, e.g., ascorbic acid (AsA), glutathione (GSH), and salicylic acid (SA), significantly accelerated the germination of aged seeds in many species, including Siberian wildrye ( Elymus sibiricus L.) [ 11 ], oat [ 13 ], and soybean ( Glycine max (L.) Merr.) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism through which priming treatments improve seed viability is related to the repair of cellular and mitochondrial components [ 11 ], synthesis of nucleic acids and proteins, and recovery of antioxidants [ 12 ]. Previous studies indicated that priming with exogenous substances, e.g., ascorbic acid (AsA), glutathione (GSH), and salicylic acid (SA), significantly accelerated the germination of aged seeds in many species, including Siberian wildrye ( Elymus sibiricus L.) [ 11 ], oat [ 13 ], and soybean ( Glycine max (L.) Merr.) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed aging is an irreversible and natural process in which the vigor of seeds declines or loses completely. Seed aging has been a popular issue in seed research, as aged seeds lower seed emergence and growth, reduce overall germination performance and limit seed production [ 1 , 2 , 3 ]. Therefore, it is of great significance to distinguish aged seeds for ensuring seed quality and reducing economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…The cycle is also involved in the regulation of plant growth and development, and the predominant role is assigned to glutathione, which has been linked to seed development [ 32 , 33 ], germination [ 20 , 34 , 35 ], and longevity [ 36 , 37 ]. Seed priming with AsA and/or GSH was found to successfully diminish aging damage in seeds [ 38 ]. Ascorbate (Asc) is less studied than its cycle partner, but its roles beyond being an antioxidant molecule have been documented [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%